Pengaruh Kemampuan Verbal dan Kemampuan Numerik terhadap Prestasi Belajar Matematika Siswa SMPS Katolik Aurora Kefamenanu - Eva Binsasi; Yuliana L. Nahak; Stanislaus Amsikan (Fakultas Pertanian, Universitas Timor, 2019)
Verbal ability and numerical ability is the competence required in learning mathematics and allegedly affect the student's mathematics learning achievement. This study aims to see whether or not the influence of verbal ability and numerical ability on mathematics learning achievement of SMP students either partially or simultaneously. The study was conducted at SMPS Catholic Kefamenanu Aurora 2017/2018. The instruments used are verbal ability test, numerical ability test and mathematics learning achievement test. The instruments used are verbal ability test, numerical ability test and mathematics learning achievement test. Based on the results of data analysis it can be concluded that : 1) Partially there is a significant influence between the ability of verbal and numerical ability to the achievement of junior high school students. 2) Simultaneously there is a significant influence between verbal ability and numerical ability to student's mathematics learning achievement. Based on these results can be concluded that both partially and simultaneously there is influence between the ability of verbal and numerical ability of student achievement of junior high.